Work-life integration among nurse educators: a meta-synthesis - Erasmus, Sonja; Downing, Charlene; Ntshingila, Nompumelelo (Frontiers in Global Women's Health, 2024)
Background: Work-life integration has been extensively researched in various contexts.Women dominate the nursing profession, but work-life integration is essential for men and women since both are expected to focus equally on their families and careers. The nursing faculty perceives nurse educators' work environment as undervalued, lacking support, and limited time to grow and carry the heavy workload.Method: A qualitative meta-synthesis of studies between 2013 and 2023 was conducted using ScienceDirect, EBSCO Host, Sage and Sabinet databases. Seven articles related to the research phenomenon were retrieved.The resulting themes revolved around two central aspects: nurse educators' work and life integration. Nurse educators face various challenges with work-life integration and often view their failure as a personal rather than a societal issue. However, as much as achieving work-life integration is personal, there is a call for employers in academic environments to improve workplace policies, like better-paid maternity leave, affordable quality childcare, and social support. Furthermore, nurse educators' line managers should display warmth and encouragement about personal challenges affecting nurse educators.